The Effectiveness of Chlorpromazine to Decrease the Level of Tumor Necrosis Factor-Alpha Serum in Schizophrenic Patients with Coronavirus Disease 2019 - Tanra, Andi Jayalangkara; Andi Sameggu, Ahmad; Renaldi, Rinvil; Bahar, Burhanuddin; Syamsuddin, Saidah; Ilyas, Muhammad; Lisal, Sonny T. (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The ongoing coronavirus disease 2019 (COVID-19) pandemic caused by the severe acute respiratory syndrome coronavirus-2. The COVID-19 pandemic has also had an impact on mental health, including those with schizophrenia (SCH). There were 131 inpatient schizophrenic patients who were confirmed positive for COVID-19 at Dadi Makassar Hospital, South Sulawesi, Indonesia, but all of these patients did not experience any clinical symptoms of COVID-19. Chlorpromazine as an antipsychotic also has antiviral and anti-inflammatory effects in schizophrenic patients with COVID-19, and the schizophrenic neuroinflammatory is very likely to occur in patients with COVID-19 infection. AIM: The researchers tried to examine the effectiveness of chlorpromazine on serum TNF-values in schizophrenic patients with COVID-19. METHODS: This research is a nested case–control study. The study was conducted on schizophrenic patients with mild and asymptomatic cases of COVID-19 at Dadi Mental Hospital with a sample of 40 patients compared to 42 schizophrenic patients who were not COVID-19. Study subjects received chlorpromazine 100 mg/day for 4 weeks. Serum tumor necrosis factor-alpha (TNF-α) concentrations were measured by enzyme-linked immunosorbent assays when COVID-19 was first confirmed and after 4 weeks. Positive and negative syndrome scale (PANSS) and clinical global impression SCH (CGI-SCH) examinations were also performed to measure the clinical symptoms of SCH. RESULTS: The comparison of baseline TNF-serum levels that increased in the schizophrenic group with COVID-19 was 9.33 pg/ml higher, compared to the schizophrenic group without COVID-19. The decrease in TNF-levels in the schizophrenic group with COVID-19 of 7.96 pg/ml (p < 0.001) indicated an improvement in TNF-serum levels at week 4. Meanwhile, there was no significant decrease in serum TNF- levels in the non-COVID-19 schizophrenic group (p > 0.05). CONCLUSION: The serum TNF-value of schizophrenic patients with COVID-19 is higher than schizophrenic patients without COVID-19. Coadministration of chlorpromazine, antipsychotics, and COVID-19 therapy reduces serum TNF- values in schizophrenic patients with COVID-19. The administration of chlorpromazine and antipsychotic in therapeutic doses reduced the total PANSS and CGI-SCH values.